2016
DOI: 10.1155/2016/7917528
|View full text |Cite
|
Sign up to set email alerts
|

Food-Derived Natural Compounds for Pain Relief in Neuropathic Pain

Abstract: Neuropathic pain, defined as pain caused by a lesion or disease of the somatosensory nervous system, is characterized by dysesthesia, hyperalgesia, and allodynia. The number of patients with this type of pain has increased rapidly in recent years. Yet, available neuropathic pain medicines have undesired side effects, such as tolerance and physical dependence, and do not fully alleviate the pain. The mechanisms of neuropathic pain are still not fully understood. Injury causes inflammation and immune responses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 128 publications
0
29
0
Order By: Relevance
“…Accordingly to Rodriguez‐Amaya et al and Rufino et al the contents of carotenoids in the mesocarp of A. aculeata surpasses of other tropical fruits. Considering the increasing demand for health‐related natural products from consumers, the nutraceutical potential natural appeal of macauba in its natural state may be considered as one of its remarkable characteristics …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly to Rodriguez‐Amaya et al and Rufino et al the contents of carotenoids in the mesocarp of A. aculeata surpasses of other tropical fruits. Considering the increasing demand for health‐related natural products from consumers, the nutraceutical potential natural appeal of macauba in its natural state may be considered as one of its remarkable characteristics …”
Section: Resultsmentioning
confidence: 99%
“…Consumers have shown an increasing demand for natural products which tends to be associated with the health‐related benefits obtained from several classes of bioactive compounds . MUFA, as well as carotenoids, tocopherols, tocotrienols, among other micronutrients, have been related to human blood cholesterol‐lowering as well as to reducing the incidence of coronary heart and various other human diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Trauma, infection, cancer, and other conditions could cause neuropathic pain. This can be characterized as spontaneous pain, allodynia (pain response from nonnoxious stimulations), and hyperalgesia (excessive reactions from noxious stimulation) [28,29]. Common histopathological and neurophysiological changes include neurodegeneration, loss of myelinated fibers, and the demyelination of myelinated fibers [30].…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Several studies also reported that nonsteroidal anti-inflammatory drugs (NSAIDs) might cause gastrointestinal lesions or renal and liver failure [4, 5]. Therefore, there is an emerging need for the discovery of novel materials for producing effective and safe analgesics [6, 7]. Many recent studies have evaluated innovative medical materials based on natural products [810].…”
Section: Introductionmentioning
confidence: 99%